DNA repair and cancer in colon and rectum: Novel players in genetic susceptibility - Pardini, Barbara; Corrado, Alda; Paolicchi, Elisa; Cugliari, Giovanni; Berndt, Sonja I; Bezieau, Stephane; Bien, Stephanie A; Brenner, Hermann; Caan, Bette J; Campbell, Peter T; Casey, Graham; Chan, Andrew T; et al. (International journal of cancer, 2020)
Interindividual differences in DNA repair systems may play a role in modulating the individual risk of developing colorectal cancer. To better ascertain the role of DNA repair gene polymorphisms on colon and rectal cancer risk individually, we evaluated 15,419 single nucleotide polymorphisms (SNPs) within 185 DNA repair genes using GWAS data from the Colon Cancer Family Registry (CCFR) and the Genetics and Epidemiology of Colorectal Cancer Consortium (GECCO), which included 8,178 colon cancer, 2,936 rectum cancer cases and 14,659 controls. Rs1800734 (in MLH1 gene) was associated with colon cancer risk (p-value = 3.5 × 10-6 ) and rs2189517 (in RAD51B) with rectal cancer risk (p-value = 5.7 × 10-6 ). The results had statistical significance close to the Bonferroni corrected p-value of 5.8 × 10-6 . Ninety-four SNPs were significantly associated with colorectal cancer risk after Binomial Sequential Goodness of Fit (BSGoF) procedure and confirmed the relevance of DNA mismatch repair (MMR) and homologous recombination pathways for colon and rectum cancer, respectively. Defects in MMR genes are known to be crucial for familial form of colorectal cancer but our findings suggest that specific genetic variations in MLH1 are important also in the individual predisposition to sporadic colon cancer. Other SNPs associated with the risk of colon cancer (e.g., rs16906252 in MGMT) were found to affect mRNA expression levels in colon transverse and therefore working as possible cis-eQTL suggesting possible mechanisms of carcinogenesis.
Keywords: senioři; Genetic Predisposition to Disease; rektum; DNA-Binding Proteins; DNA Repair Enzymes; jednonukleotidový polymorfismus; Biological Variation, Population; Male; single nucleotide polymorphisms; cancer susceptibility; Risk Assessment; Middle Aged; registrace; mužské pohlaví; studie případů a kontrol; Carcinogenesis; MutL Protein Homolog 1; Adult; mladý dospělý; biologická variabilita populace; MutL homolog 1; DNA modifikační methylasy; Registries; rectal cancer; enzymy opravy DNA; Colon; nádory tračníku; Young Adult; ženské pohlaví; nádory rekta; hodnocení rizik; nádorové supresorové proteiny; Humans; DNA repair; kolon; oprava DNA; Colonic Neoplasms; Tumor Suppressor Proteins; lidé středního věku; DNA vazebné proteiny; Rectal Neoplasms; dospělí; genome-wide association studies; genetická predispozice k nemoci; DNA Repair; Female; Aged; karcinogeneze; Rectum; colon cancer; DNA Modification Methylases; lidé; Case-Control Studies; Polymorphism, Single Nucleotide